Identifikasi Pola Ruang Taman Setra Di Desa Singakerta, Kecamatan Ubud, Kabupaten Gianyar, Provinsi Bali - SILVIA, RIKA; SUGIANTHARA, A.A GEDE; SUDARSANA, A.A. GEDE DALEM (Jurnal Arsitektur Lansekap, 2017)
The background of this research is graveyard space pattern as Balinesse Traditional Garden very unique. The uniqueness of the pattern in every area is influenced by different customs in that area. This research is intented for identifying and describing the space pattern on every graveyard in Singakerta Village. The method which used survey with observation techniques, interview, distribution of questionnaires and literature review. Sampling technique used purposive sampling by choosing public figure on the six graveyard of Singakerta Village. The complements of hardscape in Graveyard Singakerta Village is prajapati, pamuhunan and grave area (genah mendem sawa) was found in every graveyard (100%), wantilan in 70 %, the other building in 33 %. The complements of softscape were found 47 types of plant, kepah and bila found in Tunon and Singakerta, kepuh found in Tunon, Singakerta, Semana, pule and beringin found in Tunon, Singakerta, Demayu, ancak or bodi, bunut bulu, keduduk, kemiri only found in Singakerta, anggih and kepelan found in Kengetan. The conclution of this research is the space pattern of graveyard is influenced by age combination, clan, caste and amount of banjar, desa kala patra, desa mawa cara and meta-ethic conceps.